Kai kurie matematikos uždaviniai genetikoje - Radavičius, Marijus; Rekašius, Tomas; Židanavičiūtė, Jurgita (Lietuvos matematikos rinkinys, 2007)
After an introduction to genetic basics three problems are briefly discussed: microarray data analysis, a definition of noninformative DNA sequence, and genetic sequence alignment. More atention is paid toDNA sequence visualization and regularization of a genome signature.